OPTIMALISASI TEKNIK PEMERIKSAAN RADIOGRAFI UNTUK KASUS DISLOKASI SENDI SIKU DI RSUD ARJAWINANGUN KABUPATEN CIREBON - Muhammad Beni,; Annas Alkhowarizmi,; Casidi, (Journal of Innovation Research and Knowledge, 2025)
Examination of the elbow joint at the Arjawinangun Regional Hospital Radiology Installation uses basic projections according to the procedure, namely AP and Lateral with the elbow flexed 90 degrees for cooperative patients. Meanwhile, for uncooperative patients, AP projection and AP Oblique Medial Rotation are performed as a substitute for lateral projection. This aims to ensure patient comfort and avoid increasing injury to the patient. The aim of this research is to find out what projections are carried out in the Radiology Installation of Arjawinangun Regional Hospital in examining elbow joints in cases of dislocation. Apart from that, it is also to find out the radiographic results from the projections carried out. This research is a type of qualitative research with a case study approach. The data collection methods used were observation, interviews and documentation. The subjects of this research included two patients, one radiologist, two radiographers and data analysis, including data collection, data reduction and data presentation. The results of the study showed that when examining the elbow joint in cases of dislocation in the Radiology Installation of Arjawinangun Regional Hospital using a conventional DR aircraft with the patient positioned next to the examination table, the elbow joint was positioned above the detector according to the projection carried out with a vertical beam perpendicular to the detector, FFD 100 cm, and central point in the middle of the elbow joint. Radiographic results resulting from AP-Lateral projection, as well as AP-AP Oblique Medial Rotation can provide sufficient information to make a diagnosis.